2015
DOI: 10.1002/ppul.23153
|View full text |Cite
|
Sign up to set email alerts
|

New BPD predicts lung function at school age: Follow‐up study and meta‐analysis

Abstract: New treatment practices have improved survival of preterm infants and decreased airway pathology in bronchopulmonary dysplasia (BPD). Our aim was to investigate whether preterm birth, BPD, and the severity of BPD predict lung function in school children that are born in surfactant era. We studied pulmonary function of 88 school-aged children born very preterm (gestational age <32 weeks) and paired them with 88 age- and sex-matched controls born at term. Spirometry and diffusion capacity were recorded. We also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
1
13

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 30 publications
3
56
1
13
Order By: Relevance
“…As previously reported,14 all of the spirometric measurements (forced vital capacity (FVC), FEV 1 , FEV 1 /FVC ratio, peak expiratory flow, maximum expiratory flow at 50% of vital capacity (MEF 50 ) and maximum midexpiratory flow (MMEF)) and DLCO were significantly lower in children born preterm compared with term-born controls. Among children born preterm, FVC, FEV 1 , MEF 50 , MMEF, DLCO and DLCO/VA (alveolar volume) were lower in children with IUGR compared with children with appropriate in utero growth (table 2).…”
Section: Resultssupporting
confidence: 69%
“…As previously reported,14 all of the spirometric measurements (forced vital capacity (FVC), FEV 1 , FEV 1 /FVC ratio, peak expiratory flow, maximum expiratory flow at 50% of vital capacity (MEF 50 ) and maximum midexpiratory flow (MMEF)) and DLCO were significantly lower in children born preterm compared with term-born controls. Among children born preterm, FVC, FEV 1 , MEF 50 , MMEF, DLCO and DLCO/VA (alveolar volume) were lower in children with IUGR compared with children with appropriate in utero growth (table 2).…”
Section: Resultssupporting
confidence: 69%
“…12,30,41,42 We found that one quarter of children born extremely preterm responded positively to pharmacological bronchodilation, implying a therapeutic way forward. 21 Nevertheless, the post bronchodilator FEV 1 was still significantly lower in the preterm group than in controls (data not shown), indicating only partially reversible airways.…”
Section: Clinical Aspects Of the Resultsmentioning
confidence: 77%
“…The recruitment of participants and lung function measurements [13,14] and hospitalizations together with respiratory morbidity [15] have been reported previously. BPD was defined according to Jobe and Bancalari [16].…”
Section: Methodsmentioning
confidence: 99%
“…Pulmonary function tests included spirometry, which was recorded with SpiroStar USB (Medikro Oy, Kuopio, Finland), and the diffusing capacity of the lung for carbon monoxide (DLCO), total lung capacity (TLC), and residual volume (RV), which were measured by the single-breath method (with CO/He gases) with a Jaeger MasterScreen® PFT device (Viasys Healthcare GmbH, Höchberg, Germany). Measurements were performed according to the relevant guidelines as described earlier [13]. Data were standardized for height, age, and gender.…”
Section: Methodsmentioning
confidence: 99%